1994
DOI: 10.1111/j.1749-6632.1994.tb44291.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Invasion of the Mouse Pulmonary Epithelium by a Monoclonal IgA Directed against Shigella flexneri Lipopolysaccharide

Abstract: Bacteria belonging to the genus Shigellu cause a dysenteric syndrome in humans by invading the colonic mucosa.' Systemic as well as mucosal immune responses elicited in infected hosts after natural or experimental infections are directed mainly against the lipopolysaccharide and against a set of proteins associated with invasion and encoded by a 220-kb virulence plasmid.* Despite many studies, the respective role of systemic and mucosal responses in the protection against shigellosis remains to be determined.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Despite the recognized importance of anti-LPS SIgA antibodies in preventing the colonization and invasion of epithelial cells by enteric pathogens (3,9,12,27,36,37,42,44,53), the underlying mechanisms by which these antibodies function in mucosal immunity remains unclear. In this study, we have demonstrated that Sal4, an anti-LPS monoclonal IgA that was previously shown to protect mice against oral challenge with serovar Typhimurium bacteria, is a potent inhibitor of serovar Typhimurium flagellum-based motility.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recognized importance of anti-LPS SIgA antibodies in preventing the colonization and invasion of epithelial cells by enteric pathogens (3,9,12,27,36,37,42,44,53), the underlying mechanisms by which these antibodies function in mucosal immunity remains unclear. In this study, we have demonstrated that Sal4, an anti-LPS monoclonal IgA that was previously shown to protect mice against oral challenge with serovar Typhimurium bacteria, is a potent inhibitor of serovar Typhimurium flagellum-based motility.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Lines and Protein Production-Hybridoma cells producing IgAC5 (31) or IgGC20 (32) specific for Shigella flexneri serotype 5a LPS, IgASal4 specific for Salmonella typhimurium LPS (33), and IgAHNK20 specific for the respiratory syncytial virus fusion (F) glycoprotein (34) were cultured in RPMI 1640 medium supplemented with 10% fetal calf serum, 2 mM glutamine, 2 mM sodium pyruvate, 10 mM HEPES (pH 7.0), 0.1 mM folic acid, 100 units/ml penicillin, and 100 g/ml streptomycin as described (31,32). Cell cultures were conducted in Celline-350 bioreactors (Intregra Biosciences AG).…”
Section: Methodsmentioning
confidence: 99%
“…One colony was picked and cultured in Luria-Bertani medium (1% Bacto TM tryptone, 0.5% Bacto-yeast extracts (Sigma-Aldrich)) and 1% NaCl for 1 h at 37°C before being spread onto Luria-Bertani agar plates (1.5% Bacto TM Agar in Luria-Bertani medium). Bacteria grown overnight as a lawn were recovered in 0.9% NaCl, and their concentration was determined by spectrophotometry (Ultrospec 300; Pharmacia Biotech) using the following correlation: 1 A 600 corresponds to 5 ϫ 10 8 bacteria/ml (17). Preparation of Rotavirus-The bovine rotavirus (RF strain) was propagated in monkey kidney MA104 cells in presence of trypsin as described previously (18).…”
Section: Methodsmentioning
confidence: 99%